Türk hukukunda saklama sözleşmeleri - Arı, Benan (My University, 2023)
TÜRK HUKUKUNDA SAKLAMA SÖZLEŞMELERİ ÖZET Tarihsel açıdan bakıldığında insanın sahip olduklarını koruma güdüsünün bir uzantısı olarak saklama sözleşmeleri her zaman için varlık göstermiştir. Nitekim modern hukuk sistemlerindeki saklama sözleşmelerinin temelini Roma Hukukundaki depositum için getirilen düzenlemeler oluşturmaktadır. Günlük ve ticari hayatın içerisinde sıklıkla karşımıza çıkan bir sözleşmedir. Öyle ki banka hukuku açısından da önem arz etmektedir. Türk Hukukunda hem Mülga 818 sayılı Borçlar Kanunu’nda hem 6098 sayılı Türk Borçlar Kanunu’nda düzenlenmiş sözleşmelerdendir. Saklayanın, özenle saklama yükümlülüğünü ve aynen iade borcunu içeren güvene dayalı bir sözleşmedir. Kanunda genel saklama sözleşmeleri, misli şeylerin saklanması, ardiyeciye bırakma ve otel, garaj, otopark ve benzeri yerleri işletenlerle yapılan saklama sözleşmeleri olarak dört tür olarak düzenlenmiştir. Genel saklama sözleşmeleri uygun düştüğü ölçüde diğer saklama sözleşmelerine de esas teşkil etmektedir. Çalışmamızda saklama sözleşmesi bir bütün olarak ele alınmış ve ilgili bölümlerde her bir saklama sözleşmesinin özelliklerine yer verilmeye çalışılmıştır. Türk Hukukunda saklama sözleşmelerinin özellikleri ortaya konulurken mülga 818 sayılı Borçlar Kanunu ile mehaz İsviçre Borçlar Kanunu’ndan da faydalanılmış benzerlik ve farklılıklara yer verilmiştir. Ayrıca Fransız Medeni Kanunu’ndaki saklama sözleşmesi hükümleri ile karşılaştırmalı olarak incelenmiştir. Saklama sözleşmesi, depositum, saklayan, banka, muhafaza.

BAILMENT CONTRACTS IN TURKISH LAW ABSTRACT Bailment contracts has always been present, as an instrument for humans as a result of instinct to protect in an historical perspective. Hence, the foundation of bailment contracts in modern law was built by regulations upon depositum originating back to Roman Law. These are such contracts that are often used in both daily and commercial lives, and are of an essence in banking law. In Turkish Law, both abolished Code of Obligations No. 818 and the substitute Turkish Code of Obligations No. 6098 included this contract type. Bailee will have a liability to carefully preserve and to restitute in kind, forming a fiduciary contract between parties. In both codes, there are four types of bailment contract types, one of which is general bailment contracts, followed by bailment of fungibles, warehouse business, contracts done with hotels, garages and parking lots. As long as it is to an appropriate extent, general bailment contracts is the basis for the remaining types. In this work of ours, bailment contracts are taken as a whole, including characteristics of every other type in related chapters. Upon doing so, abolished Code of Obligations No. 818 and the reference Swiss Code of Obligations were also considered, along with their similarities and differences. Furthermore, comparative inspection of provisions from French Civil Code relating to bailment contracts is also included. lment contract, depositum, bailee, bank, preservation
Bailment contracts in Turkish law
Keywords: bailee; Bailment contract; bank; banka; Borçlar hukuku; depositum; Hukuk; Law; muhafaza; Obligations (Law); preservation; Saklama sözleşmesi; saklayan; Turkey; Türkiye